The Effect of Computational Thinking and Gender on Social Problem Solving Learning Outcomes - Riyadi, Slamet; Santosa, Eka Budhi (Jurnal Pendidikan Progresif, 2023)
The Effect of Computational Thinking and Gender on Social Problem Solving Learning Outcomes. Objective: to see the relationship between students' level of computational thinking (CT) on learning outcomes in solving social problems. Metode: using descriptive verification method with advanced analysis of K-Means clustering. Finding: Male and female learning outcomes are significantly different, where female students on average have higher learning outcomes. CT Men and Women there is no significant difference. There is a significant relationship between CT variables and learning outcomes to solve problems. The results of the K-Means analysis showed that Cluster 3 was a group of women with moderate CT levels and high learning outcomes, while cluster 4 was a group of men with moderate CT levels and moderate learning outcomes. Conclusion: female students have higher learning outcomes than male students; there is no significant relationship between CT level and gender; and the results of the K-Mean clustering analysis found 8 clusters.   Keywords: computational thinking, gender, learning outcomes.DOI: http://dx.doi.org/10.23960/jpp.v13.i3.202309